Analisis Kemampuan Berpikir Kombinatorika Siswa Kelas XII MA Wahid Hasyim Dalam Memecahkan Soal Terapan Materi Peluang Kombinasi - Wahyuni, Indah; F, Luk Luk Ainul Iffah; Nikmatuzzahro, Afina; Febiani, Devita Indri (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2019)
Combinatoric thinking is a type of thinking ability that students need to master. The combinatorics approach to thinking offers organized steps to solve problems. The purpose of this research is to ascertain the method students use to combine their thinking to solve combinations of problem opportunities. This research combines descriptive and qualitative research. Tests and interviews are the tools used. Six students from one class are the subject of this investigation. Each step of combinatorics thinking ability is represented by six students. Indicators of the application of students' combinatoric thinking skills are able to describe what is understood about the concept of combination opportunities and communicate the concept of combination opportunities. In the case of combination opportunities, students are able to write what is asked. Students can solve combination probability problems until they find solutions and answers. By using the notion of probability combinations students are able to answer questions about the order of combination opportunities. They can explain the reasons or reasons for their answers. First grade students usually have the ability to write down what is known and the questions asked correctly. Second grade students usually have the ability to replace questions that are known and asked at level one with mathematical sentences. Students at level three are more likely to do well with calculations and concept-based problems, and students at level four are more likely to be able to articulate and explain work results.